Delving into Institutional Diversity Messaging: A Cross-Institutional Analysis of Student and Faculty Interpretations of Undergraduate Experiences of Equity, Diversity, and Inclusion in University Websites - Rankin, Joanna C; Pearl , Andrew J.; Jorre de St Jorre , Trina; McGrath , Moriah M.; Dyer , Sarah; Sheriff, Samiah; Armitage , Roberta; Ruediger, Kerstin; Jere, Anoushka; Zafar , Saania; Sedres, Shalaine; Chaudhary, Daania (Teaching and Learning Inquiry, 2022)
Recognizing that university statements about equity, diversity, and inclusion are often cosmetic, performative, or at best, aspirational, rather than indicative of on-campus realities, this project analyzes interpretations of student identity and diversity through publicly available materials. The primary purpose of this research was to investigate how university messages about equity, diversity, and inclusion, available through public websites, are interpreted by faculty and students. Using a students-as-partners approach, we identified and analyzed themes based on our own perceptions and understandings of each of five university websites University of Calgary (Canada), University of Alabama (USA), Deakin University (Australia), University of Exeter (UK), and Portland State University (USA). While equity, diversity, and inclusion are signature initiatives at many universities, we found that analyses of their websites suggest that the ways in which those are operationalized differ. The patterns identified suggest that messaging through university websites can promote or detract from equity, diversity, and inclusion in university settings, and we observed differences in the ways in which institutions operationalized and represented initiatives related to equity, diversity, and inclusion. Exploring how these efforts at our five institutions are messaged to and interpreted by students provides a better understanding of the institutional priorities and the assumed values identified by student co-researchers. The use of student co-researchers proved an especially valuable contribution to this analysis to gain perspectives about presentations of student identity and diversity. Using this form of embedded research, we identify the limited presentations of and perceptions around diversity at institutions of higher education cited by student co-researchers.